Management teams' regulatory foci and organizational units' exploratory innovation: The mediating role of coordination mechanisms. Issue 5 (October 2017) - Tuncdogan, Aybars; Boon, Ad; Mom, Tom; Van Den Bosch, Frans; Volberda, Henk
Abstract : We further current understanding about the role of management teams in driving exploratory innovation by proposing that the regulatory focus of an organizational unit's management team is a key antecedent of the unit's level of exploratory innovation, and by clarifying the organizational coordination mechanisms through which this antecedent generates the unit's exploratory innovation. Our results, based on a survey of 748 managers from 69 organizational units of a large multinational semiconductor company, indicate that the promotion focus of a unit's management team relates positively to the unit's exploratory innovation. In contrast, prevention focus has a marginal negative effect. These effects are mediated by the management team's use of decentralization and connectedness. Our research advances theory development regarding the micro-foundations of organizational innovation and increases our understanding of how the views of a unit's management team are reflected in the unit's level of exploratory innovation and therefore impact the unit's chances of survival.